2013
DOI: 10.1002/jgra.50445
|View full text |Cite
|
Sign up to set email alerts
|

Type III bursts produced by power law injected electrons in Maxwellian background coronal plasmas

Abstract: [1] Simulations are presented for coronal type III bursts produced by injection of energetic electrons with power law speed spectra onto open magnetic field lines embedded in an otherwise unmagnetized Maxwellian background coronal plasma, including quasi-linear wave-particle interactions and nonlinear wave-wave processes. The simulations show that although fast electrons with speeds > 0.3c are injected, they are important only to the onset and not to the peak of f p emission, where f p is the local electron pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 75 publications
(234 reference statements)
2
19
0
Order By: Relevance
“…The spread in the observed drift rates is too large to make any meaningful conclusions about whether multiple power-laws over different frequency ranges, used by , would be a better fit rather than a single power-law fit. The drift rates are also similar to simulated type III bursts at 85 MHz and > 100 MHz by Li et al (2008); Li & Cairns (2013).…”
Section: Drift Ratesupporting
confidence: 87%
See 1 more Smart Citation
“…The spread in the observed drift rates is too large to make any meaningful conclusions about whether multiple power-laws over different frequency ranges, used by , would be a better fit rather than a single power-law fit. The drift rates are also similar to simulated type III bursts at 85 MHz and > 100 MHz by Li et al (2008); Li & Cairns (2013).…”
Section: Drift Ratesupporting
confidence: 87%
“…The velocity of electron beams, as derived from type III bursts, has been reported to be slowing down as the beams propagate through the heliosphere (Fainberg et al 1972;Krupar et al 2015;Reiner & MacDowall 2015). The drift rate has been investigated using the onset time rather than the peak time observationally (Fainberg et al 1972;Dulk et al 1987;Reiner & MacDowall 2015) and numerically (Li & Cairns 2013) and a faster velocity was obtained, postulating that the front of the electron beam travels with a faster velocity. Derived electron beam velocities are also dependent upon the conditions of the background plasma, with Li & Cairns (2014) showing how a background Kappa distribution resulted in faster derived velocities than when the background had a Maxwellian distribution.…”
Section: Introductionmentioning
confidence: 99%
“…The simulations were restricted to frequencies above 150 MHz and the type III flux peaked above 200 MHz, which is inconsistent to the general trend of increasing flux with decreasing frequency reported in this and other studies. A further study by Li & Cairns (2013) demonstrated via an initial power-law electron beam that decreasing the power-law spectral index increased the fundamental radio flux emitted at high and low radio frequencies. Both sets of simulations can explain why a coronal burst produced by an electron beam with a smaller (harder) power-law spectral index, i.e.…”
Section: Interplanetary Bursts and >25 Kev Electronsmentioning
confidence: 99%
“…The first theory of plasma emission was put forth by Ginzburg & Zhelezniakov (1958) and many modifications and improvements have been made over the past six decades (Tsytovich 1967;Kaplan & Tsytovich 1968;Zheleznyakov & Zaitsev 1970;Melrose 1982;Goldman & Dubois 1982;Goldman 1983;Cairns 1987;Robinson & Cairns 1998;Mel'Nik et al 1999;Kontar 2001;Ledenev et al 2004;Li et al 2005Li et al , 2006aLi et al ,b, 2008aLi & Cairns 2013;. Although the essential theoretical framework based upon EM weak turbulence theory, which describes the entire process starting from the beam-generated Langmuir turbulence to the radiation generation, was available, complete numerical solution of the entire set of EM weak turbulence equations have not been done until quite recently, when Ziebell et al (2014aZiebell et al ( ,b,c, 2015 numerically solved the complete equations of EM weak turbulence theory for the first time.…”
Section: Introductionmentioning
confidence: 99%